2013
DOI: 10.3758/s13423-012-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Flexible and fast: Linguistic shortcut affects both shallow and deep conceptual processing

Abstract: Previous research has shown that people use linguistic distributional information during conceptual processing, and that it is especially useful for shallow tasks and rapid responding. Using two conceptual combination tasks, we showed that this linguistic shortcut extends to the processing of novel stimuli, is used in both successful and unsuccessful conceptual processing, and is evident in both shallow and deep conceptual tasks. Specifically, as predicted by the ECCo theory of conceptual combination, people u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 23 publications
10
79
0
Order By: Relevance
“…Liu et al (2018) explored the mechanism in more detail by introducing a competing measure of ease of simulation (i.e., a normed variable that reflects how easily a phrase could result in a coherent simulation of meaning) and comparing its effect to that of distributional cooccurrence frequency in metaphor processing. Following Connell and Lynott (2013), Liu et al found that people were more likely to reject a sentence as nonsensical when the constituent words seldom co-occurred across language (e.g., illness can be bright) compared to when they co-occurred more often (e.g., supply can be bright), and additionally showed that this effect occurred independently of ease of simulation. The speed of rejection, however, was more LABELS IN CONCEPTUAL PROCESSING 21 complex.…”
Section: Available Processing Resourcesmentioning
confidence: 99%
See 3 more Smart Citations
“…Liu et al (2018) explored the mechanism in more detail by introducing a competing measure of ease of simulation (i.e., a normed variable that reflects how easily a phrase could result in a coherent simulation of meaning) and comparing its effect to that of distributional cooccurrence frequency in metaphor processing. Following Connell and Lynott (2013), Liu et al found that people were more likely to reject a sentence as nonsensical when the constituent words seldom co-occurred across language (e.g., illness can be bright) compared to when they co-occurred more often (e.g., supply can be bright), and additionally showed that this effect occurred independently of ease of simulation. The speed of rejection, however, was more LABELS IN CONCEPTUAL PROCESSING 21 complex.…”
Section: Available Processing Resourcesmentioning
confidence: 99%
“…Humans do not have infinite executive and memory resources to devote to conceptual processing, and so it would greatly enhance cognitive efficiency if there were some form of triage mechanism available that could flag up at an early stage when a particular conceptual process is likely to prove excessively difficult and is not worth further effort. Connell and Lynott (2013; propose that the linguistic shortcut can offer such a cognitive triage mechanism. Since concepts that are often discussed in the same context are likely to be easily integrated in a shared situation , linguistic distributional information from concept labels offers a guide to the likelihood of successful simulation.…”
Section: Available Processing Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…A likely possibility, consistent with how other concepts are represented, is that multiple representations work together, including grounding, compressed abstractions, and distributed linguistic representations (e.g., Andrews, Frank, & Vigliocco, 2014;Barsalou, Santos, Simmons, & Wilson, 2008;Connell & Lynott, 2013;Louwerse, 2011;Paivio, 1986).…”
Section: Abstractionmentioning
confidence: 99%